16q22.1 microdeletion and anticipatory guidance. Issue 7 (29th May 2019) - Abdullah, Sarah; Helal, Mayada; Dupuis, Lucie; Stavropoulos, D. James; Louro, Pedro; Ramos, Lina; Mendoza‐Londono, Roberto
Abstract: The widespread availability of comparative genomic hybridization (CGH) array analysis has led to the discovery of several genomic microdeletion‐associated syndromes and has identified possible genetic causes for patients with previously unexplained clinical features. We report the case of four unrelated patients who share common clinical characteristics, namely failure to thrive, developmental delay, dysmorphic features, and congenital anomalies. CGH array analysis revealed that all four patients had a de novo microdeletion at 16q22.1. In this case report, we describe the clinical features of these patients and offer possible explanations for how their 16q22.1 microdeletion may account for their symptoms. We also suggest guidelines for the management of 16q22.1 microdeletion based on the phenotypes seen in our patients and the function of the genes affected by this microdeletion.